Renewing industrialization strategies in Africa - Kormawa, Patrick; Jerome, Afeikhena (International Food Policy Research Institute, 2015)
This chapter reviews Africa’s effort toward the renewal of industrialization over the past several years and proposes a new approach to industrial policy for Africa. The chapter is divided into five sections. After this introduction, the second section builds a case for Africa’s industrialization and assesses the current state of the industry. Section 3 introduces the past industrial strategies and their outcomes. Section 4 provides an outline for a new industrial policy for Africa.